Gating of the two‐pore cation channel AtTPC1 in the plant vacuole is based on a single voltage‐sensing domain. (12th July 2016) - Jaślan, D.; Mueller, T. D.; Becker, D.; Schultz, J.; Cuin, T. A.; Marten, I.; Dreyer, I.; Schönknecht, G.; Hedrich, R.
Abstract: The two‐pore cation channel TPC1 operates as a dimeric channel in animal and plant endomembranes. Each subunit consists of two homologous Shaker‐like halves, with 12 transmembrane domains in total (S1‐S6, S7‐S12). In plants, TPC1 channels reside in the vacuolar membrane, and upon voltage stimulation, give rise to the well‐known slow‐activating SV currents. Here, we combined bioinformatics, structure modelling, site‐directed mutagenesis, and in planta patch clamp studies to elucidate the molecular mechanisms of voltage‐dependent channel gating in TPC1 in its native plant background. Structure‐function analysis of the Arabidopsis TPC1 channel in planta confirmed that helix S10 operates as the major voltage‐sensing site, with Glu450 and Glu478 identified as possible ion‐pair partners for voltage‐sensing Arg537. The contribution of helix S4 to voltage sensing was found to be negligible. Several conserved negative residues on the luminal site contribute to calcium binding, stabilizing the closed channel. During evolution of plant TPC1s from two separate Shaker‐like domains, the voltage‐sensing function in the N‐terminal Shaker‐unit (S1‐S4) vanished.